1998
DOI: 10.1042/bj3330811
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional structure of a class-Pi glutathione S-transferase complexed with glutathione: the active-site hydration provides insights into the reaction mechanism

Abstract: The structure of mouse liver glutathione S-transferase P1-1 complexed with its substrate glutathione (GSH) has been determined by X-ray diffraction analysis. No conformational changes in the glutathione moiety or in the protein, other than small adjustments of some side chains, are observed when compared with glutathione adduct complexes. Our structure confirms that the role of Tyr-7 is to stabilize the thiolate by hydrogen bonding and to position it in the right orientation. A comparison of the enzyme-GSH str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
3
13
0
1
Order By: Relevance
“…Tyr-7, which is conserved in all cytosolic GSTs, is an essential residue for catalytic activity (41,42). The structure of mouse GST confirms that the role of Tyr-7 is to stabilize the thiolate by hydrogen bonding and to position it in the right orientation (40). Asp-98, an evolutionally conserved aspartyl residue across the dimer interface, participates in GSH recognition (7,11,43).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Tyr-7, which is conserved in all cytosolic GSTs, is an essential residue for catalytic activity (41,42). The structure of mouse GST confirms that the role of Tyr-7 is to stabilize the thiolate by hydrogen bonding and to position it in the right orientation (40). Asp-98, an evolutionally conserved aspartyl residue across the dimer interface, participates in GSH recognition (7,11,43).…”
Section: Discussionmentioning
confidence: 78%
“…The highly specific G-site for binding GSH is formed by Tyr-7, Arg-13, Trp-38, Lys-44, Gln-51, Leu-52, and Ser-65 from one subunit and Asp-98 from the other subunit (7,10,11,40,41). Tyr-7, which is conserved in all cytosolic GSTs, is an essential residue for catalytic activity (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Dimeric shikonin and three-dimensional structure of p-GST had been determined by nuclear magnetic resonance spectroscopy [30] and crystallography [31]; our shikonin-GST binding assays suggested that a homology dimer GST might bind with 20 monomeric or 10 dimeric shikonins.…”
Section: Discussionmentioning
confidence: 98%
“…2B). The domains I and II form G-site (GSH binding site) and H-site (xenobiotic binding site), respectively [28] specifically for detoxification purpose. The arrangement of a/b in both domains in such a manner reflects the structural conservation between species which might be due to the execution of similar functions The overall frequency of different structural patterns detected in BmGST by PyMOL 1.0 [29] were 54.8% helix, 9.6% sheet, 13% turn, 19.2% coil and 3.4% 3-10 helix which is in accordance with an earlier report [30].…”
Section: Resultsmentioning
confidence: 99%